PROGRAM MENCIPTAKAN MANFAAT BERSAMA UNTUK MENINGKATKAN PENDAPATAN PETANI PISANG DI KABUPATEN TANGGAMUS, PROVINSI LAMPUNG - Rofi, Abdur (Analisis Kebijakan Pertanian, 2021)
The Creating Shared Value (CSV) program as an alternative to the Corporate Social Responsibility (CSR) program provides options that allow companies to increase competitiveness while stimulating inclusive growth in reducing the poverty of farming families. This study examines the CSV program by looking at farmers’ interests and the impact of the CSV program on banana commodities in Tanggamus Regency, Lampung Province. This study uses primary data obtained from surveys of 60 partner and non-partner farmers and in-depth interviews with 18 people involved in the existing business model. This research was conducted in March-April 2020. The data were analyzed descriptively. The results showed that the CSV program had been implemented in the location. In this CSV program, farmers get assistance from the company and certainty of selling banana products at an agreed price. However, not all farmers are interested in the program for various reasons, including due to limited land, limited time available, and farmers who do not want to be bound by work agreements. The impact of the CSV program on the banana commodity on household farmers’ income has not been significant because bananas are not the primary source of livelihood for household farmers. The policy implication is that the CSV program can be an alternative to CSR programs. However, the success of this program also needs to consider the profile and the sources of livelihoods of farmers to ensure that farmers’ interest and involvement can be more optimal. ABSTRAK Program Menciptakan Manfaat Bersama (CSV) sebagai alternatif dari program Corporate Social Responsibility (CSR) memberikan pilihan bagi perusahaan untuk meningkatkan daya saing sekaligus merangsang pertumbuhan inklusif dalam pengurangan kemiskinan keluarga petani. Penelitian ini bertujuan mengkaji program CSV dengan melihat minat petani dan dampak program CSV pada komoditas pisang di Kabupaten Tanggamus, Provinsi Lampung. Penelitian ini menggunakan data primer yang diperoleh dari survei ke 60 petani mitra dan nonmitra, serta melalui wawancara mendalam dengan 18 orang pelaku yang terlibat di dalam model bisnis. Penelitian ini dilakukan pada bulan Maret‒April 2020. Analisis data dilakukan secara deskriptif. Hasil penelitian menunjukkan bahwa program CSV sudah dijalankan untuk komoditas pisang Cavendish di Tanggamus, Provinsi Lampung. Dalam program ini, petani mendapatkan bantuan bibit tanaman pisang, akses bantuan kredit untuk pembelian saprodi, dan kepastian penjualan hasil tanaman pisang dengan harga yang disepakati. Namun demikian, tidak semua petani berminat dalam program kemitraan dengan berbagai alasan, antara lain dikarenakan keterbatasan lahan, keterbatasan waktu yang dimiliki, dan petani tidak ingin terikat dalam perjanjian kerja. Dampak program CSV pada komoditas pisang terhadap pendapatan petani belum cukup besar karena pisang bukan komoditas utama sumber penghidupan petani. Program CSV dapat menjadi alternatif program CSR, namun keberhasilan program ini juga perlu mempertimbangkan profil dan juga sumber penghidupan petani untuk memastikan minat dan keterlibatan petani dapat lebih optimal.